Rare Cancers in Children – The EXPeRT Initiative: A Report from the European Cooperative Study Group on Pediatric Rare Tumors - Bisogno, G.; Ferrari, A.; Bien, E.; Brecht, I. B.; Brennan, B.; Cecchetto, G.; Godzinski, J.; Orbach, D.; Reguerre, Y.; Stachowicz-Stencel, T.; Schneider, D. T. (Klinische Pädiatrie, 2012)
The low incidence and the heterogeneity of very rare tumors (VRTs) demand for international cooperation. In 2008, EXPeRT (European Cooperative Study Group for Pediatric Rare Tumors) was founded by national groups from Italy, France, United Kingdom, Poland and Germany. The first aims of EXPeRT were to agree on a uniform definition of VRTs and to develop the currently most relevant scientific questions. Current initiatives include international data exchange, retrospective and prospective studies of specific entities, and the development of harmonized and internationally recognized guidelines. Moreover, EXPeRT established a network for expert consultation to assist in clinical decision in VRTs.
Keywords: rare tumors; epidemiology; children; network; orphan disease